2017
DOI: 10.1002/cncr.30769
|View full text |Cite
|
Sign up to set email alerts
|

Delays in breast cancer diagnosis after a state policy limiting Medicaid enrollment

Abstract: There currently is great interest in understanding the benefits and harms associated with Medicaid expansions and contractions. The Patient Protection and Affordable Care Act expanded eligibility for Medicaid to individuals and families with incomes up to 138% of the federal poverty level (FPL), although the Supreme Court later made this Medicaid expansion voluntary (to date, 31 states and the District of Columbia have expanded their Medicaid programs). More recently, the American Health Care Act considered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Due to the hidden nature of breast cancer symptoms at early stage, most patients come to the hospital at the middle or late stage of breast cancer, missing the best treatment opportunity. Early diagnosis and treatment are essential for better prognosis (2). The preferred diagnostic method for breast cancer is color Doppler ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hidden nature of breast cancer symptoms at early stage, most patients come to the hospital at the middle or late stage of breast cancer, missing the best treatment opportunity. Early diagnosis and treatment are essential for better prognosis (2). The preferred diagnostic method for breast cancer is color Doppler ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Due to the delay in diagnosis, the number of patients with advanced breast cancer has increased. Previous studies have shown that early diagnosis of breast cancer can significantly improve the survival rate of patients, [ 3 ] but the current clinical lack of effective means of early screening. Studies have confirmed that breast cancer has genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%